Ultrasonic-assisted extraction of thiols from garlic bulbs - Ismail, Nur Izzah; Hashim, Yumi Zuhanis Has-Yun; Jamal, Parveen; Mohd Salleh, Hamzah; Othman, Rashidi (AENSI Publications, 2014)
Cysteine and glutathione (GSH) are important low molecular mass thiols or sulfhydryl compounds that play numerous important roles in metabolism. They also have myriads of applications in industry including pharmaceutical, cosmetic and foods. These compounds naturally occur in plants but less was focused on extracting them from plant sources. Garlic is of particular interest as potential source for thiol compounds since it contains high concentration of organosulfur which correlates with the presence ofcysteine and GSH. In this work, water-based ultrasonic assisted extraction was used toextract thiols from garlic bulbs. The effect of garlic concentration and amplitude of sonicator on thiol concentration was investigated. The optimal garlic concentration of 10 % (w/v) was able to extract 0.170 mMthiols and 100 % amplitude of sonicator corresponds to the highest value of thiol compounds obtained.